(untitled) (International Journal of Engineering and Computer Science, 2014)
Security issues for software system ultimately concern relationships among social actors, stakeholders, system users, potential attackers and the software acting on their behalf. The tools and methodologies providing systematic guidance and support to the design process are much needed. Data in its original form typically contains sensitive information about individual, and publishing such data will violate individual privacy. The current practice in data publishing relies mainly on policies and guidelines as what types of data can be published. This paper presents A Survey on Privacy Preserving Homomorphic in Collaborative data Publishing that are found in the current literature. Problems in usage of privacy preserving areas are identified. Security areas that needed future research are presented